Out of the wild night : a ghost story - Balliett, Blue, 1955- (New York : Scholastic Press, 2018)
Mary W. Chase died on Nantucket Island just over one hundred years ago, but she is still there, in the house she once lived in, and she wants to keep it that way--but first she must some how contact a group of children who are interested in preserving historic homes on the island.
School Library Journal, January 2018
Publisher's Weekly, January 2018
Kirkus Starred, December 2017
Booklist, December 2017
5.3
3-6
Keywords: Haunted houses -- Juvenile fiction; Historic preservation -- Juvenile fiction; Nantucket Island (Mass.) -- Juvenile fiction; Haunted houses -- Fiction; Historic preservation -- Fiction; Nantucket Island (Mass.) -- Fiction; Ghost stories